1998
DOI: 10.1023/a:1023291921695
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The tear film plays an important role in the defense of the external ocular surface. During sleep a number of changes take place, including increased production and release of various inflammatory mediators. We have studied the hypothesis that closed-eye tears contain proinflammatory cytokines and lipid inflammatory mediators, which serve to recruit polymorphonuclear leukocytes (PMNs) and regulate the function of PMNs and IgA during sleep. We investigated interleukin-1beta, interleukin-6, interleukin-8, monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…We found that the levels of IL-10, IL-13, IL-17, IFN γ , and CCL5 were lower in the closed-eye tears, while the level of CXCL8 was higher at eye opening when compared to the values measured 30 mins later. These findings are in line with numerous studies showing alterations in tear fluid composition after awakening [ 1 , 3 , 10 , 14 , 16 , 17 ]. During sleep or eye closure, physiological changes occur in the ocular surface causing a local subclinical inflammatory state [ 1 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the levels of IL-10, IL-13, IL-17, IFN γ , and CCL5 were lower in the closed-eye tears, while the level of CXCL8 was higher at eye opening when compared to the values measured 30 mins later. These findings are in line with numerous studies showing alterations in tear fluid composition after awakening [ 1 , 3 , 10 , 14 , 16 , 17 ]. During sleep or eye closure, physiological changes occur in the ocular surface causing a local subclinical inflammatory state [ 1 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…A specific diurnal alteration pattern of IL-1 β , IL-6, CXCL8, IL-10, IL-12p70, and TNF α has been found showing the importance of the timing of tear collection during the day [ 2 ]. It is noteworthy that the examination of different cytokines present in overnight tears has been reported mainly in control [ 1 , 10 ] and allergic eyes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PD-L1 protects the ocular surface from T-cell-mediated damage in murine models of corneal transplant and dry eye disease [62–65]. However, decreased tear production and clearance during disease of the LFU or in the closed eye during sleep cause the levels of inflammatory mediators in tears to increase, which may compromise ocular surface homeostasis [53,66,67]. …”
Section: Immunoregulation Of the Ocular Mucosamentioning
confidence: 99%
“…This may relate to factors mentioned above or could result from the combination of tear film alteration by the contact lens and tear film changes that take place in a closed-eye situation. 6871 Both appear to be independent factors that occur during lid closure; however, the relationship between the two is not as well defined. A contact lens, regardless of material, will alter the environment and therefore the ocular surface when worn on a regular basis.…”
Section: Dry Eye Ocular Surface Inflammation and Corneal Infectionmentioning
confidence: 99%